A two‐enzyme immobilization approach using carbon nanotubes/silica as support. (15th November 2014) - Du, Kun; Sun, Jian; Zhou, Xiaoyu; Feng, Wei; Jiang, Xia; Ji, Peijun
<x xml:space="preserve">Abstract</x> Multiple enzyme mixtures are attractive for the production of many compounds at an industrial level. We report a practical and novel approach for coimmobilization of two enzymes. The system consists of a silica microsphere core coated with two layers of individually immobilized enzymes. The model enzymes α‐amylase (AA) and glucoamylase (GluA) were individually immobilized on carbon nanotubes (CNTs). A CNT‐GluA layer was formed by adsorbing CNT‐GluA onto silica microsphere. A sol‐gel layer with entrapped CNT‐AA was then formed outside the CNT‐GluA/silica microsphere conjugate. The coimmobilized α‐amylase and glucoamylase exhibited 95.1% of the activity of the mixture of free α‐amylase and glucoamylase. The consecutive use exhibited a good stability of the coimmobilized enzymes. The developed approach demonstrates advantages, including controlling the ratio of coimmobilized enzymes in an easy way, facilitating diffusion of small molecules in and out of the matrix, and preventing the leaching of enzymes. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:42–47, 2015